Industrial IoT smartbox for the shop floor - Malhão, Sérgio (2019)
Constant search for efficiency and productivity has led to innovation on the factory shop floor, representing an evolution of the current production systems combined with new technologies of industrial automation and information technology. This work presents an experimental demo of a smartbox for Industry 4.0 scenarios, allowing sensing, monitoring and data acquisition. We have tested two different approaches, depending on the communication protocol used for real time applications: OPC UA or MQTT. Raspberry Pi’s platform act as an OPC UA server or MQTT broker, respectively. From the measurements, data stored in a cloud server can be accessed remotely with improved security and visualized from a computer dashboard. One of the conclusions that can be drawn is that both protocols allow data from the smartbox to be stored and easily monitored from a smartphone application or a computer web interface. MQTT is a good option in communications requiring very low bandwidth. However, there is a lack of suitable libraries to program alarm features for OPC UA Servers.